POTENSI DAN DAMPAK EKONOMI DARI EKSTENSIFIKASI CUKAI BAHAN BAKAR MINYAK - Purwanto, Didik; Setyawan, Budhi (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
Fuel oil (BBM) is a non-renewable fuel whose use has caused various negative impacts on the environment and society. As time goes by, fuel reserves in the world are also decreasing due to continuous extraction from nature. The government needs to implement policies that can control fuel consumption in order to reduce the negative impacts caused by fuel use while maintaining oil reserves available in nature. This research aims to analyze the potential and economic impact of implementing excise tax on fuel in Indonesia. Qualitative analysis was conducted by comparing fuel excise implementation in other countries and evaluating criteria for excisable goods. Quantitative analysis utilized potential analysis, excise instrument effectiveness analysis, and economic impact analysis using the Input-Output method across 185 sectors. The findings indicate that fuel exhibits inelastic characteristics, where a 1% increase in fuel prices results in a 0.04% decrease in demand. The implementation of fuel excise has the potential to increase state revenue by 7.84% to 23.51%. The resulting economic impacts include a reduction in final demand for fuel, an increase in fuel prices, and a reduction in pollutant emissions. Apart from that, the implementation of fuel excise also has an impact on increasing gross value added, worker compensation and business surplus.